Cirrhosis increases complication rate and overall mortality in patients with traumatic lung injury. (July 2019) - Grigorian, Areg; Albertson, Spencer; Delaplain, Patrick T; Gabriel, Viktor; Maithel, Shelley; Dosch, Austin; Schubl, Sebastian; Joe, Victor; Nahmias, Jeffry
Introduction: Hepatic cirrhosis is associated with an increased mortality in trauma. However, the association between cirrhosis and outcomes in traumatic lung injury has not been investigated. We hypothesize that cirrhosis adversely affects mortality and increases complications after traumatic lung injury. Methods: A retrospective analysis of the National Trauma Data Bank was performed between 2007 and 2015. Patients ≥ 18 years of age with traumatic lung injury were identified and grouped by the presence or absence of cirrhosis. Patients that died in the emergency department or those with a severe (grade > 3) abbreviated injury scale for head trauma were excluded. The primary outcome was mortality. Results: Out of 6, 774, 260 patients, 578, 883 (8.5%) presented with traumatic lung injury. Of these, 1971 (0.3%) had a concomitant diagnosis of cirrhosis. The cirrhotic group was significantly older (median age, 56 versus 42 years, p < 0.001) and more likely to be hypotensive on admission (9.3% versus 6.7%, p < 0.001). There was no difference in injury severity score (p > 0.05). Patients with cirrhosis had a significantly longer median length of stay (12.5 versus 8.8 days, p < 0.001), rates of acute kidney injury (7.6% versus 1.4%, p < 0.001), acute respiratory distress syndrome (7.3% versus 2.9%, p < 0.001), pneumonia (12.9% versus 5.9%, p < 0.001), and overall mortality (20.6% versus 5.6%, p < 0.001). After adjusting for significant covariates, cirrhosis (OR = 6.26, 95% CI = 5.49–7.14, p < 0.001) was found to be an independent risk factor for mortality in patients with traumatic lung injury. Conclusion: Cirrhosis in patients with traumatic lung injury is associated with more than a sixfold higher risk of mortality and increased rates of complications such as acute kidney injury and acute respiratory distress syndrome. While much focus has been on increased mortality of cirrhosis in patients with concomitant abdominal solid organ or traumatic brain injury, our study suggests cirrhosis with traumatic lung injury to possibly be an even worse prognosticator.